Romantisasi Kesedihan dalam Representasi Kota pada Lirik Bandung Hari Ini - Dimas Satrio Wijaksono; Freddy Yusanto; Jalesita Putri Pramitha (UPT Publikasi Ilmiah Unisba, 2026)
Abstact. This study analyzes the romanticization of sadness in the representation of the city in the lyrics of the song “Bandung Hari Ini” by For Revenge using Roland Barthes’s semiotics. From a cultural communication perspective, lyrics are understood as cultural texts that produce social meaning through a system of signs. The study employs an interpretive qualitative approach by identifying signifiers and signifieds, denotative and connotative meanings, cultural codes, as well as myths and ideologies. The results show that, denotatively, the lyrics represent exhaustion, loneliness, pain, unfulfillment, a journey, and a return. Connotatively, Bandung is interpreted as a space of nostalgia, a sense of security, homecoming, and emotional healing. Cultural codes regarding homecoming, the demands of adult success, urban mobility, self-care, and the aesthetics of melancholy shape the myth of Bandung as an “emotional home.” The lyrics also convey an ideology of urban productivity and naturalize sadness as an authentic and meaningful experience. The novelty of this research lies in the construction of urban space as a repository of memory, identity, homecoming, and hope. Abstrak. Penelitian ini menganalisis romantisasi kesedihan dalam representasi kota pada lirik lagu Bandung Hari Ini karya For Revenge menggunakan semiotika Roland Barthes. Dalam perspektif komunikasi budaya, lirik dipahami sebagai teks budaya yang memproduksi makna sosial melalui sistem tanda. Penelitian menggunakan pendekatan kualitatif interpretatif dengan mengidentifikasi penanda dan petanda, makna denotatif, konotatif, kode budaya, serta mitos dan ideologi. Hasil penelitian menunjukkan bahwa secara denotatif lirik merepresentasikan kelelahan, kesepian, luka, ketidakcapaian, perjalanan, dan kepulangan. Secara konotatif, Bandung dimaknai sebagai ruang nostalgia, rasa aman, kepulangan, dan pemulihan emosional. Kode budaya mengenai kepulangan, tuntutan keberhasilan usia dewasa, mobilitas urban, perawatan diri, dan estetika melankolia membentuk mitos Bandung sebagai “rumah emosional”. Lirik juga membawa ideologi produktivitas urban serta menaturalisasi kesedihan sebagai pengalaman autentik dan bermakna. Kebaruan penelitian terletak pada konstruksi ruang kota sebagai penyimpan memori, identitas, kepulangan, dan harapan.